If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+6)-13=43+2x+12
We move all terms to the left:
4(x+6)-13-(43+2x+12)=0
We add all the numbers together, and all the variables
4(x+6)-(2x+55)-13=0
We multiply parentheses
4x-(2x+55)+24-13=0
We get rid of parentheses
4x-2x-55+24-13=0
We add all the numbers together, and all the variables
2x-44=0
We move all terms containing x to the left, all other terms to the right
2x=44
x=44/2
x=22
| -3x+4x+1=-(-x-1) | | 7x-(9x2)=5x(-6) | | 5x+41=(-2x)+48 | | -4f+24+14=20 | | 4r=-12+8r | | 3/5y=-40 | | 8-x*3=6 | | 2(x-7)+(3x-1)=4x+3 | | -27-9=7x-21-6 | | 3x-8=6x-16 | | 2=3÷x=-10 | | 5x-2x=7+3x-7 | | 104=a-82 | | -4-(2+3x=18 | | 8+5a=7a | | 22p=44 | | 3(w+7)-7w=-15 | | (5x+4)+(7x-18)=118 | | 12x+7=29 | | 35x+700=40x+100 | | 5x-2x=+3x-7 | | -2k+7=-7 | | (2x+1)^2=4x^2+1 | | 24y=24y | | −12y-9+7y=26 | | 3(y+16)=3y-34 | | 5x-2+10*2=96 | | 5+3k=5(1-8k) | | 5s=4.5 | | 5+1v=8+.75v | | 60-3x+15*2=102 | | 4y+101–4y–33=54–8y–50 |